Evaluasi peraturan kawasan merokok bagi pegawai negeri sipil di Boalemo, Gorontalo - Sudarmi I Popa; Fatwa Sari Tetra Dewi; Laksono Trisnantoro (Berita Kedokteran Masyarakat (BKM), 2016)
Evaluation of the implementation of the smoking area banning regulations on smoking behavior of government officials in Boalemo, GorontaloPurposeThis study aimed to investigate implementation of regional regulations for banning smoking on employees smoking behavior in a government office in Boalemo. MethodsThis research used a qualitative approach with a case study design involving 23 subjects. Data collection used systematic observation, regulatory documents, in-depth interviews and focus group discussions. ResultsBackground process of drafting rules were, 1) idea of regent, 2) translation of indicators of clean and health living behavior, 3) Ministry of Health, 4) illness and death data caused by smoking, and 5) impact of smoking. Effectiveness of policy implementation for area smoking ban was largely determined by, 1) input: availability of facilities dedicated to smoking area, effort control, labeling, guidance system and form of communication channel, 2) process: leadership support, stakeholder involvement, social norm, legal regulation regent, monitoring, and evaluation. Rules indirectly provide positive effect for output of small portion of employees in terms of, 1) intention to quit smoking, 2) frequency of smoking in room reduced, and 3) there were some employees who quit smoking. ConclusionImplementation of a policy was determined by: 1) role of leader as indicator of example and role model for subordinates, 2) support and role of all relevant stakeholder, and 3) social norms that encouraged positive behavioral changes in smoking.